Edukasi Pencegahan Bullying pada Anak di Sekolah Dasar Negeri Kresek - Suheri Suheri; Rangga Wahyu Fattahillah; Maharani Yusuf Putri; Aura Syamsa (Universitas Pahlawan Tuanku Tambusai, 2026)
Bullying is a serious issue that negatively affects children's psychological, social, and academic development. The high number of bullying cases in schools highlights the importance of early prevention efforts. Therefore, students participating in the Community Service Program (KKN) of Universitas Tangerang Raya conducted an anti-bullying socialization program at SD Negeri Kresek 1. The activity employed interactive lectures and role-playing methods to improve students' understanding of bullying. Interactive lectures were used to explain the definition, types, and impacts of bullying, while role-playing provided realistic simulations of bullying situations commonly encountered in school environments. The program involved 48 students from classes 6A and 6B. The results indicated an improvement in students' understanding of bullying, its negative consequences, and appropriate ways to prevent and report such behavior. In addition, the activity fostered empathy, courage, and social skills among students. This program is expected to support the creation of a safe, comfortable, and bullying-free school environment.